Clinical Symptoms on Covid-19 Patient According to Pregnancy Status - Anita Rahmawati; Pertiwi Perwiraningtyas (Universitas Muhammadiyah Pekajangan Pekalongan, 2023)
Physiological adaptation in pregnant women may increase the risk of more severe symptoms of Covid-19 than women who are not pregnant but there was not much supporting data. Aim of this study was to compare the severity category between women who are pregnant and not pregnant with positive Covid-19. The study was conducted using a retrospective approach which obtained secondary data from patient medical records after being tested positive for COVID-19 from November 2020 to December 2021. Sample size for the study consisted of 67 women COVID-19 patients who were pregnant and 67 women who were not pregnant. Samples were taken by accidental sampling. Categorization of clinical symptoms of COVID-19 was divided into 5 categories (no symptoms, mild, moderate, severe/severe pneumonia, critical). Data were analysis with the Mann Whitney test. Results showed that there were significant differences in the categories of clinical symptoms between groups of pregnant women and groups of non-pregnant women who were exposed to Covid-19 with a value of p=0.000 (p<0,05). Clinical symptoms in Covid-19 patients who are pregnant more severe than women who are not pregnant. This may be caused by increased levels of coagulation and fibrinolytic factors during pregnancy. It is hoped that the handling of Covid-19 patients, especially pregnant women, will receive more detailed attention to avoid the appearance of more severe clinical symptoms.